Kinerja Aparatur Pemerintah Desa Dalam Pelayanan Administrasi Kependudukan (Studi pada kantor kepala Desa Godean Kecamatan Loceret Kabupaten Nganjuk) - purnamasari, sefty yuli (Jurnal Administrasi Publik, 2014)
Abstract: Apparatus Village Government Performance in Service Population Administration (Studies in the District Office of the Chief of the Village Godean Loceret Nganjuk). Apparatus Performance is an important role in the functioning of the service. The performance level is divided into three individual performance, the performance of the process and organizational performance. The results showed that the performance of government officials in the ministry of rural population administration at the village head's office Godean, sub loceret, Nganjuk been good this can be seen from the quantity of work the village government officials can complete the work in accordance with the needs of the community. Quality of service is good village government officials this is evidenced by the efficiency and satisfaction in a community population administration invoke services. Work completed village government officials can be completed on time in accordance with that is planned or has been listed in the rules. There are 3 supporting the infrastructure and facilities, comfortable work environment, and the cooperation between devices. There are 3 inhibitor that is about the lack of reliable use of IT, lack of coordination between RT and RW field and the quality of education of the village. To overcome the problems occurred, suggestions to improve device performance needs to be improved is the village that the village administration capabilities through the provision of training, skill formation as administrative personnel for the village that is not only reliable in carrying out tasks that are routine but can also be a driver of a rural development. Keywords: Performance apparatus, village government, population services administration, godean. Abstrak: Kinerja Aparatur Pemerintah Desa Dalam Pelayanan Administrasi Kependudukan (Studi Di Kantor Kepala Desa Godean Kecamatan Loceret Kabupaten Nganjuk). Kinerja Aparatur memang peranan penting dalam fungsi pelayanan. Tingkat kinerja dibagi menjadi tiga yaitu kinerja individu, kinerja proses dan kinerja organisasi. Hasil penelitian menunjukkan bahwa Kinerja aparatur pemerintah desa dalam pelayanan administrasi kependudukan di kantor kepala desa godean, kecamatan loceret, kabupaten nganjuk sudah baik hal ini dapat dilihat dari kuantitas pekerjaan aparatur pemerintah desa dapat menyelesaikan pekerjaannya sesuai dengan kebutuhan masyarakat. Kualitas layanan aparatur pemerintah desa sudah baik hal ini dibuktikan dengan efisiensi dan kepuasan masyarakat dalam memohon layanan administrasi kependudukan. Pekerjaan yang diselesaikan aparatur pemerintah desa dapat selesai tepat waktu sesuai dengan yang telah direncakanan atau yang tercantum dalam aturan. Terdapat 3 pendukung yaitu sarana dan prasarana, Lingkungan kerja yang nyaman dan adanya kerjasama antar perangkat. Terdapat 3 penghambat yaitu tentang kurangnya penggunakan IT yang handal, Kurangnya koordinasi lapangan antara RT dan RW dan kualitas pendidikan perangkat desa. Untuk mengatasi permasalahan yang terjadi, saran untuk meningkatkan kinerja perangkat desa yang perlu ditingkatkan adalah kemampuan administrasi desa melalui pemberian pelatihan, keterampilan sebagai pembentukan tenaga-tenaga administrasi bagi desa yang tidak hanya handal dalam menjalankan tugas-tugas yang bersifat rutin tetapi juga bisa mrnjadi penggerak suatu pembangunan desa. Kata Kunci: Kinerja aparatur, pemerintah desa, pelayanan administrasi kependudukan, godean